Local Development in Cameroon Under the Constraint of Own Resources: the Case of the Municipalities in the Far North Region - Marcel, Gouenet (EuroEconomica, 2023)
The problem of this paper stresses on the low contribution of self-generated resources of each municipality as a trap for underdevelopment of the local economy in Cameroon. The methodological approach was based on secondarys datasin other to make a flat tri analysis. Like in most rural communal councils in major part of the Far-North Region in general and the Mayo- Kani Division in particular are largely dependent on financed with the FEICOM and governments grants. The results of statistical highlight not only the constrains linked to the lack of own financial resources, but also a low mobilisation of local taxation income and the lack of qualified human resources among the communal personel. This hampers diverse infrastructural development as well as the local development process itself.